Assessing the Devastating Impact of Climate Change on Biodiversity - Clifford, Anariochi Bright; Kikka, Helen; Chike, Enyinda (American Journal of Biodiversity, 2026)
Climate change poses an unprecedented threat to global biodiversity, compromising ecosystem resilience, disrupting species interactions, and exacerbating extinction risk. This comprehensive study synthesizes evidence from ecological, physiological, and genetic perspectives to investigate the devastating impact of climate change on biodiversity. Our analysis reveals alarming declines in species populations, altered community compositions, and compromised ecosystem resilience. Rising temperatures, altered precipitation patterns, and increased frequency of extreme events disrupt species’ adaptations, interactions, and habitats. Human activities, particularly greenhouse gas emissions, drive climate change, with far-reaching consequences for ecosystem services and human well-being. This study highlights the urgent need for climate action, emphasizing climate-smart conservation strategies, ecosystem resilience enhancement, and climate change research and monitoring.